2015
DOI: 10.1007/s10549-015-3372-9
|View full text |Cite
|
Sign up to set email alerts
|

miR-218 targets survivin and regulates resistance to chemotherapeutics in breast cancer

Abstract: Multidrug resistance (MDR) remains one of the most significant obstacles in breast cancer treatment, and this process often involves dysregulation of a great number of microRNAs (miRNAs). Some miRNAs are indicators of drug resistance and confer resistance to chemotherapeutic drugs, although our understanding of this complex process is still incomplete. We have used a combination of miRNA profiling and real-time PCR in two drug-resistant derivatives of MCF-7 and Cal51 cells. Experimental modulation of miR expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 49 publications
3
63
0
1
Order By: Relevance
“…Transfected cells were collected, counted and resuspended in single cell suspension (FBS-free culture medium). Subsequently, 1x10 5 cells were added to the upper chamber and 500 µl culture medium supplemented with 20% FBS, was added into the lower chamber as a chemoattractant. Following a 24 h incubation, any non-migrated cells were carefully removed from the top of the chamber using a cotton swab.…”
Section: Cell Migration and Invasion Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Transfected cells were collected, counted and resuspended in single cell suspension (FBS-free culture medium). Subsequently, 1x10 5 cells were added to the upper chamber and 500 µl culture medium supplemented with 20% FBS, was added into the lower chamber as a chemoattractant. Following a 24 h incubation, any non-migrated cells were carefully removed from the top of the chamber using a cotton swab.…”
Section: Cell Migration and Invasion Assaymentioning
confidence: 99%
“…The etiology of breast cancer remains unclear, although genetic and epigenetic alterations are considered to contribute to tumorigenesis and progression (4). Despite advances in modern therapies for patients with breast cancer, including surgery, radiotherapy, hormonal therapy and various types of chemotherapeutic approaches using targeted and non-targeted drugs, numerous patients with breast cancer respond only transiently to conventional chemotherapy (5,6). A high proportion of these patients eventually exhibit tumor metastasis, which is a major contributor to cancer mortality (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that miR-218 is involved in breast cancer evasion of apoptosis by targeting survivin (26). This molecule has been targeted for therapy in cancer based on its selective expression in tumors, but not normal tissues (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…miRNA-218 (miR-218) is expressed in many cancers and plays critical roles in carcinogenesis, including in proliferation and apoptosis (Hu et al, 2015;Liu et al, 2015;Ran et al, 2015;Xie et al, 2015;Zhang et al, 2015b). Its function in gastric cancer has also been investigated.…”
Section: Introductionmentioning
confidence: 99%